Entry Island - May, Peter, 1951- (Quercus, 2015)
When a murder rocks the isolated community of Entry Island, insomniac homicide detective Sime Mackenzie boards a light aircraft at St. Hubert airfield bound for the small, scattered chain of Madeline Islands, in the Gulf of St. Lawrence, as part of an eight-officer investigation team from Montréal.